KEARIFAN LOKAL DALAM PEMBANGUNAN STUDI KASUS: REVITALISASI BANGUNAN TRADISIONAL DI ILAGA, KABUPATEN PUNCAK - PAPUA - Zebua, Mercyana Trianne; Salipu, M Amir; Utomo, Sugito (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2022)
Development activities including structuring traditional areas that have been going on for the past two decades are often carried out only based on economic considerations and area functions. The more dominant tendency is to ignore considerations of traditional and historical values. There is a shift towards social and cultural values along with a global phenomenon, namely the absorption of economic or financial benefits. This shift in values has an impact on changes in the built environment, such as changes in the face of the environment, both from the environmental and building aspects. Therefore this revitalization activity aims to revive the traditional values and history of the area in the form of traditional building arrangements. The method used is the literary method by conducting a study on several literary sources in the form of reports on revitalization activities and articles related to local wisdom and revitalization of traditional areas. The results obtained show that there are changes in the area that tend to bring out traditional values in the buildings resulting from the revitalization of the area which are appreciated by the people who observe the results of this revitalization activity. The conclusion that can be seen is that visible efforts to revive traditional and historic values in the form of traditional buildings in the development area are enough to give the area an image as a traditional area.